Snow data assimilation‐constrained land initialization improves seasonal temperature prediction. Issue 21 (9th November 2016) - Lin, Peirong; Wei, Jiangfeng; Yang, Zong‐Liang; Zhang, Yongfei; Zhang, Kai
Abstract: We present the first systematic study to quantify the impact of land initialization on seasonal temperature prediction in the Northern Hemisphere, emphasizing the role of land snow data assimilation (DA). Three suites of ensemble seasonal integrations are conducted for coupled land‐atmosphere runs. The land component is initialized using datasets from (1) no DA, (2) assimilating Moderate Resolution Imaging Spectroradiometer (MODIS) snow cover fraction (SCF), and (3) assimilating both MODIS SCF and Gravity Recovery and Climate Experiment (GRACE) terrestrial water storage. Results show that snow DA improves temperature predictions especially in the Tibetan Plateau (by 5–20%) and high latitudes. Improvements at low latitudes are seen immediately and last up to 60 days, whereas improvements at high latitudes only appear later in transitional seasons. At high latitudes, assimilating GRACE data results in marked and prolonged improvements (by ~25%) due to large initial snow mass changes. This study has great implications for future land DA and seasonal climate prediction studies. Key Points: Using snow DA‐constrained land initialization improves seasonal temperature prediction in the Northern Hemisphere The impacts of snow DA depend on latitude and lead time At high latitudes, GRACE DA offers marked additional improvements compared to MODIS DA